Dampak Riba terhadap Pembangunan Ekonomi Berkelanjutan: Perspektif Islam dan Teknologi - Ayu, Alina Naura; Agustin, Voni Nilla; Fitriyani, Ashly Indah; Rafifah, Rifda Asla; Putri, Devana Yulia; Puspitasari, Wening Octavia; Nurrohim, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sustainable economic development is an important global goal in the modern era, where the balance between economic growth, social justice, and environmental preservation is key. One major challenge in achieving this goal is the practice of usury (riba), which negatively impacts economic stability and creates injustice. From an Islamic perspective, riba is considered a cause of economic injustice that hinders the creation of a fair and inclusive economic system. Therefore, this paper explores the impact of riba on sustainable economic development and the role of technology, particularly fintech, as a solution that aligns with sharia principles. Sharia fintech can offer fair and efficient alternatives in the financial system, support inclusive economic growth, and reduce social inequality. However, challenges in implementing sharia-based technology need to be addressed through appropriate regulations, technological infrastructure, and public education. By combining technology and Islamic values, it is hoped that a more just and sustainable economic system can be created.